ChemInform Abstract: Small Head‐to‐Tail Macrocyclic α‐Peptoids. Issue 43 (21st October 2014) - Culf, Adrian S.; Cuperlovic‐Culf, Miroslava; Leger, Daniel A.; Decken, Andreas
Abstract Head‐to‐tail macrocyclization of α‐peptoid acids provide α‐peptoides such as the product (II) in high yields.